Cancellation in Systems: An Empirical Study of Task Cancellation Patterns and Failures - Sethi, Utsav; Pan, Haochen; Lu, Shan; Nath, Suman; Musuvathi, Madan (OSDI, 2022)
Modern software applications rely on the execution and coordination of many different kinds of tasks. Often overlooked is the need to sometimes prematurely terminate or cancel a task, either to accommodate a conflicting task, to manage system resources, or in response to system or user events that make the task irrelevant. In this paper, we studied 62 cancel-feature requests and 156 cancel-related bugs across 13 popular distributed and concurrent systems written in Java, C#, and Go to understand why task cancel is needed, what are the challenges in implementing task cancel, and how severe are cancel-related failures. Guided by the study, we generalized a few cancel-related anti-patterns, and implemented static checkers that found many code snippets matching these anti-patterns in the latest versions of these popular systems. We hope this study will help guide better and more systematic approaches to task cancellation.